MUHAMMAD ABID AL-JABIRI - Nurliana Damanik (UIN Sumatera Utara, 2019)
Bayani is a method of typical Arabic thought that is based on the authority of the text (nash), directly or indirectly, directly means understanding the text as finished knowledge and directly applying it without the need for thought; indirectly means understanding the text as raw knowledge so that it needs interpretation and reasoning. However, this does not mean that reason or ratio can freely determine the meaning and purpose, but still must rely on the text. Knowledge of irfan is not based on texts such as bayani, but on reality, the secrets of reality are revealed by God. Therefore, irfani knowledge is not obtained based on text analysis but by spiritual practice, where with purity of heart, it is expected that God will bestow knowledge directly on him. Thus, the source of burhani knowledge is ratio, not text or intuition. It is this ratio that provides judgment and decisions on information that enters the senses.